All in the Family: Extension Editors Aren't Perfect Either - Jack Belck (Journal of Applied Communications, 1973)
While traveling about the state, helping county extension staffers work up efficient, hard-hitting publicity, PR and advertising for their local efforts, it dawned on me that many of the bad examples I told them about came from material extension editors had prepared.